Spain and Morocco: from the Disaster of Annual to Primo de Rivera’s dictatorship (1921-1930). Coordinated by Rocío Velasco de Castro. An Introduction - Velasco de Castro, Rocío (Hispania Nova, 2021)
This text offers a historical introduction and presents the state of the art in which the contributions that make up this special issue called “Spain and Morocco: from the Disaster of Annual to Primo de Rivera’s dictatorship (1921-1930)” are inscribed. It is a brief period, barely a decade, in which the Moroccan problem formed the backbone of Spanish political life. After the defeat of Spanish troops in Annual the growing influence of the Army and what happened in the Moroccan protectorate in the national and international politics of those years were revealed. This interaction will be approached from different perspectives through a series of original works that would aim to contribute to the study of a key stage in contemporary History of Spain.